Mammography Diagnosis and Pathological Analysis - Lanyi, Marton (Springer Berlin Heidelberg, 2003)
Mammography can be thought of as a (sub)macroscopic "shadow pathology" - confident diagnosis necessitates comprehensive knowledge of breast pathology. The traditional rules of thumb, for example that a regular, rounded shadow means a benign lesion, a radiating structure represents a malignant tumor, and microcalcification indicates biopsy, no longer hold true. This volume aims to explain modern breast pathology to physicians practicing mammography. The over 600 individual illustrations and more than 1,000 references help the reader understand breast morphology. The book is rounded off by a detailed description of the clinical symptoms and a helpful summary of the supplementary diagnostic procedures and the possibilities for treatment